TOP VISIONARIES WHO CHANGED THE WORLD - ILIAN, GEORGE (Mumbai Jaico Publishing House, 2018)
What if you could sit down to dine with some of the world$1 (Bs most successful entrepreneurs and have a conversation with them? What would you ask them? What insights would they give to you? Find inspiring life and business lessons from visionaries such as Steve Jobs, Mark Zuckerberg, Warren Buffett, and Tony Robbins, Elon Musk and Oprah Winfrey. Without passion for what you are doing, you will not make it very far in your field. Read about success and failure from visionary leaders who have built some of the most valuable organizations of the world. http://www.jaicobooks.com/j/j_searchtry.asp?selcat=title&keyword=Top+visionariess
Keywords: Business Personalities; Elon Musk; Bill Gates; Steve Jobs; Mark Zuckerberg; Jack Ma; Warren Buffett